Non‐templated assembly of D5h‐symmetric Pd5L10 rings by precise ligand angle adjustment - Neukirch, Laura; Kulas, Milan D.; Holstein, Julian J.; Clever, Guido H. (Wiley, 2024)
We report a series of Pd(II)nL2n coordination rings for which nuclearity is controlled by the binding angle of the corresponding bis-monodentate bridging ligands. Judicious choice of the angle within a family of rather rigid ligands allowed for the first-time to synthesize a homoleptic five-membered Pd5L10 ring that does not require any template to form. We demonstrate that control over the ring size is maintained both in the solid-, solution-, and gas-phase. Two X-ray structures of five-membered rings from ligands with ideal angles (yielding a perfect pentagonal ring) vs. suboptimal angles (resulting in a highly distorted structure) illustrate the importance of the correct ligand geometry. A mathematical model for estimating the expected ring size based on the ligand angle was derived and DFT computations show that ring-strain is the major factor determining the assembly outcome.
Chemistry - a European journal; 30(27)
Keywords: Self-assembly; Ligand design; Supramolecular chemistry; Solvent effects; Fivefold symmetry; 540